PENGARUH PRENATAL YOGA TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III - Fitri Adriani; Khusnul Makrifatus Sholikhah; Aina; Suratmi (Universitas Batam, 2022)
During pregnancy, a pregnant woman experiences several changes in her body, both physically which includes changes in her body shape, weight gain, and psychologically. Where the various changes are the consequences that must be borne from the growth of the fetus in the womb. Anxiety is a condition that involves emotional which can be observed from physiological stimuli, unpleasant feelings of tension to fear of something. Yoga activities carried out during pregnancy can make pregnant women more focused in dealing with childbirth later, where doing yoga can help in tolerating pain and converting stress and anxiety into energy. The method used in this study is to find data analysis by using studies or literature reviews by looking for journals or articles that have relevance to the influence of prenatal yoga on the anxiety level of pregnant women in the third trimester. Where from the results of the literature review, it was found that there was an influence of prenatal yoga on the anxiety of pregnant women in the third trimester. From the results obtained, in handling anxiety and increasing the readiness of pregnant women in the delivery process, it is necessary to give prenatal yoga exercises regularly and according to the program as a form of intervention from midwifery care which is a therapeutic option that can be done by third trimester pregnant women